Design, Synthesis, and In Vitro and In Vivo Biological Studies of a 3′-Deoxythymidine Conjugate that Potentially Kills Cancer Cells Selectively - Wei, Qiong; Zhang, Dejun; Yao, Anna; Mai, Liyi; Zhang, Zhiwei; Zhou, Qibing (PLOS ONE, 2012)
Thymidine kinases (TKs) have been considered one of the potential targets for anticancer therapeutic because of their elevated expressions in cancer cells. However, nucleobase analogs targeting TKs have shown poor selective cytotoxicity in cancer cells despite effective antiviral activity. 3′-Deoxythymidine phenylquinoxaline conjugate (dT-QX) was designed as a novel nucleobase analog to target TKs in cancer cells and block cell replication via conjugated DNA intercalating quinoxaline moiety. In vitro cell screening showed that dT-QX selectively kills a variety of cancer cells including liver carcinoma, breast adenocarcinoma and brain glioma cells; whereas it had a low cytotoxicity in normal cells such as normal human liver cells. The anticancer activity of dT-QX was attributed to its selective inhibition of DNA synthesis resulting in extensive mitochondrial superoxide stress in cancer cells. We demonstrate that covalent linkage with 3′-deoxythymidine uniquely directed cytotoxic phenylquinoxaline moiety more toward cancer cells than normal cells. Preliminary mouse study with subcutaneous liver tumor model showed that dT-QX effectively inhibited the growth of tumors. dT-QX is the first molecule of its kind with highly amendable constituents that exhibits this selective cytotoxicity in cancer cells.